Mini-review: microbiota have potential to prevent PEDV infection by improved intestinal barrier - Yang, Shanshan; Liu, Guangliang; Savelkoul, Huub F. J.; Jansen, Christine A.; Li, Bin (Frontiers in Immunology, 2023)
Porcine epidemic diarrhea virus (PEDV) infection poses a significant threat to the global pig industry. Current prevention and control strategies are inadequate in protecting pigs from new PEDV variants. This review aims to examine the relationship between PEDV and intestinal microbes, and investigate whether modulating intestinal microbes could affect PEDV infection. The mechanisms by which various intestinal microbes affect viral infection were initially introduced. Intestinal microbes can influence enteric viral infection through direct contact, such as binding, or by affecting interferons (IFNs) production and the intestinal barrier. Influencing the intestinal barrier by microbes can impact PEDV infection in young piglets. To narrow down the range of microbes that may influence PEDV infection, this review summarized microbes that change after infection. Short chain fatty acids (SCFAs), bacterial cell components, and toxins from microbes were identified as important mediators affecting PEDV infection. SCFAs primarily strengthen the intestinal barrier and inhibit intestinal inflammation, while bacterial cell components and toxins are more likely to damage the intestinal barrier. Therefore, this review hypothesizes that fecal transplantation, which allows the host to colonize more SCFAs-producing microbes, may prevent PEDV infection. However, these hypotheses require further proof, and the transplantation of intestinal microbes in pigs requires more exploration.